2022
DOI: 10.1177/23259671211052069
|View full text |Cite
|
Sign up to set email alerts
|

Concussions in the National Hockey League: Analysis of Incidence, Return to Play, and Performance

Abstract: Background: Concussion injuries are common in professional hockey; however, their effect on player performance remains unclear. Purpose: To quantify the effect of concussions on the performance of position players in the National Hockey League (NHL). Study Design: Cohort study; Level of evidence, 3. Methods: Concussion data from the NHL were collected using publicly available databases for the seasons between 2009-2010 and 2015-2016, coinciding with new NHL concussion rules. Age, body mass index, position, num… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…One patient died in hospital (<1%) after severe TBI (Table 4). Median hospital LOS was 2 [1][2][3] days and median ICU LOS was 2 [1-2] days.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One patient died in hospital (<1%) after severe TBI (Table 4). Median hospital LOS was 2 [1][2][3] days and median ICU LOS was 2 [1-2] days.…”
Section: Discussionmentioning
confidence: 99%
“…1 Despite this enthusiasm and relatively robust literature on the sport in many ways, national-level analyses of patient demographics, clinical characteristics, and injury data are lacking. In hockey and other contact sports, attention has recently been given to injury prevention, especially in terms of head, 2,3 face, 4-7 and mouth 8-10 injuries. Helmets, visors, and mouthguards are frequently required to play hockey, as injuries can be sustained via a number of different mechanisms including falling on the ice or into the boards, puck strike, or contact with another player.…”
Section: Introductionmentioning
confidence: 99%
“…As for professional sports, A 2018 study on concussion numbers in National Football League (NFL) reported an average greater than one concussion for every two games [ 36 ]. While a 2022 study reported concussion prevalence in the National Hockey League (NHL) to be one concussion for every 17 games [ 37 ].…”
Section: Introductionmentioning
confidence: 99%
“…Because of the intense physical nature of hockey, many players will experience some injury during their career, many of which will be significant enough to cause missed game time. 2 Of these injuries, concussions are prevalent, with an incidence of up to 5.8 to 6.1 per 100 games. 2 , 3 Concussions are considered a form of mild traumatic brain injury, and the pathogenic mechanism involves diffuse axonal injury due to the shearing of axons in the brain.…”
mentioning
confidence: 99%
“… 2 Of these injuries, concussions are prevalent, with an incidence of up to 5.8 to 6.1 per 100 games. 2 , 3 Concussions are considered a form of mild traumatic brain injury, and the pathogenic mechanism involves diffuse axonal injury due to the shearing of axons in the brain. 29 Overall, concussions have short-term, severe effects on performance 18 , 24 and cause long-lasting changes in both cerebrovascular and cognitive function.…”
mentioning
confidence: 99%